The Relationship Between Anthelmintic Therapy Compliance and The Health Status and Quality of Life of Young Adults - Muhamad Sulthan Tanjung; Ali Napiah Nasution; Qori Fadillah (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2026)
Helminth infection remains a significant public health concern that may affect the health status and quality of life of young adults living in high-risk areas. However, this productive age group is often under-represented in soil-transmitted helminth (STH) research. This study aims to examine the relationship between adherence to anthelmintic therapy and both health status and quality of life among young adults in the working area of UPT Puskesmas Stabat. An analytic cross-sectional design was employed. A total of 47 young adults (aged 18–25 years) with a history of anthelmintic therapy in the previous 6–12 months were recruited through purposive sampling. Adherence was assessed using the modified 8-item Morisky Medication Adherence Scale (MMAS-8), health status with a validated complaints questionnaire combined with objective Body Mass Index (BMI) measurement, and quality of life with the WHO Quality of Life-BREF (WHOQOL-BREF) instrument covering the physical, psychological, social, and environmental domains. Data were analyzed using the chi-square test (with Yates correction or Fisher’s exact test where appropriate) on collapsed 2×2 tables, complemented by odds ratios (ORs) with 95% confidence intervals (CIs) and the phi coefficients.  Most respondents were female (57.4%), aged 22–25 years (51.1%), students (55.3%), and had a normal BMI (68.1%). Adherence was high in 68.1% and moderate in 31.9% of respondents; 61.7% had good health status and 72.3% reported high quality of life. Adherence was not significantly associated with health status (χ² = 2.11; p = 0.147; OR = 2.51, 95% CI 0.71–8.86; φ = 0.21). In contrast, adherence was strongly and significantly associated with quality of life (Fisher’s exact p < 0.001; φ = 0.90). Within the limitations of a cross-sectional design, higher adherence to anthelmintic therapy was associated with better quality of life but not with measurable health status. Strengthening adherence through education and health-promotion efforts may therefore enhance the quality of life of young adultsKeywords: Anthelmintic Therapy Adherence; Health Status; Quality of Life; Young Adults; Soil-Transmitted Helminth